2021
DOI: 10.1111/phn.12922
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 vaccine hesitancy among women leaving jails: A qualitative study

Abstract: In many correctional facilities across the United States, COVID‐19 vaccine refusal rates are as high as 50%. Most women leaving jails have low SES, health literacy, and mistrust of governmental institutions, thus exacerbating existing health disparities and making women leaving jail vulnerable. Data from 25 interviews with recently released women suggest that interventions to promote vaccines to this population will have to address health education and mitigate mistrust, misinformation, and conspiracy theories. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
56
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(60 citation statements)
references
References 10 publications
3
56
0
1
Order By: Relevance
“…In other words, participants who expressed not wanting a COVID-19 vaccine perceived themselves at relatively low risk of a severe SARS-CoV-2 infection. Other studies have confirmed similar findings; younger incarcerated people were less likely to accept a COVID-19 vaccine [33] , [34] , [36] , [37] , [38] , [39] . Conversely, older participants with concomitant comorbidities expressed a greater interest in vaccination, recognizing their heightened risk of severe disease.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…In other words, participants who expressed not wanting a COVID-19 vaccine perceived themselves at relatively low risk of a severe SARS-CoV-2 infection. Other studies have confirmed similar findings; younger incarcerated people were less likely to accept a COVID-19 vaccine [33] , [34] , [36] , [37] , [38] , [39] . Conversely, older participants with concomitant comorbidities expressed a greater interest in vaccination, recognizing their heightened risk of severe disease.…”
Section: Discussionsupporting
confidence: 69%
“…Secondly, as with all qualitative studies, volunteer, sampling, and social desirability biases may have been introduced. While there are limitations, this study adds to the dearth of literature vis-à-vis COVID-19 vaccine hesitancy among people in prison [36] . By contrasting participants’ lived experiences and highlighting patterns across their opinions, this study provides empirically-grounded evidence for our understanding of COVID-19 vaccine acceptability and hesitancy for incarcerated individuals.…”
Section: Discussionmentioning
confidence: 99%
“…That said, similar reasons for vaccine hesitancy have been reported in the Canadian general population, suggesting that social desirability bias was minimal [ 54 , 55 ]. Despite these limitations, this study is an important contribution to the scarce literature on COVID-19 vaccine refusal among incarcerated individuals [ 56 ] and may be generalizable to other correctional settings outside Canada and to populations who may share similar sociodemographic characteristics such as people who inject drugs, homeless communities, and migrants.…”
Section: Discussionmentioning
confidence: 99%
“… Fridman et al, 2021 , Teherani et al, 2021 , Akel et al, 2021 , Romer and Jamieson, 2021 , Keene Woods et al, 2021 , Ma and Ma, 2021 , Roberts et al, 2021 , Mondal et al, 2021 , Patil et al, 2021 , Rabin and Dutra, 2021 , Olanipekun et al, 2021 , Okoro et al, 2021 , Johnson et al, 2021 , Jacob et al, 2021 , Carson et al, 2021 , Bogart et al, 2021 , Rodriguez et al, 2021 , Ciardi et al, 2021 , Savoia et al, 2021 , Ofei-Dodoo et al, 2021 , Zheng et al, 2021 , Sharma et al, 2021 , Baniak et al, 2021 , Geana et al, 2021 , Hirshberg et al, 2021 , Rungkitwattanakul et al, 2021 .…”
Section: Uncited Referencesmentioning
confidence: 99%